SCREENING AND OBESITY DAGNOSTIC TEST WITH BOELECTRICAL IMPEDANCE ANALYSIS AND INELASTIC GAUGE ON COLLEGE STUDENT IN EAST JAVA - Roselya Mutiara Pratiwi; Ni Luh Putu Arum Puspitaning Ati (Sekolah Ilmu Kesehatan Dan Ilmu Alam (SIKIA), Universitas Airlangga, 2020)
Backgound: Measurement of body fat percentage as estimates of obesity, which can be done with the method of measuring the bioelectrical impedance analysis (BIA) and the meter inches inelastic. Both of these methods can be used as a simple, safe and non-nvasive. Objective: To analyze the comparative measurement of obesity with the BIA and the meter inches inelastic. Method: The study was observational analytic with cross sectional design. Sample were taken and selected through simple ramdomize sampling method. Data obtained directly by measuring samples that met the inclusion criteria. Obesity screening data obtained by measuring the percentage of body fat using BIA method and meter inches inelastic. Results: Based on the calculationn, as many as 65 samples taken by proportional random sampling in each specialization the student of the Faculty of Public Health 2014 Airlangga University. The percentage of female students with obesity using the BIA was 29,2% and inelastic inch meter is 21,5%. The statistical test showed t test was 0,897 ( sig>0,05). Conclusion: There are differences in the measurement result mean obesity BIA metered inches inelastic screening tools and have a good validity in measuring obesity. Suggestion : For further research it is recommended to be more accurate in measuring using an inelastic inch meter, while when using BIA it should use altimeter measurement because it is needed for data input.